Estetika Irama dan Etika dalam Syi’ir Ber-Qafiyah Lam Karya Harits Al-Makhzumi (Analisis Arudh dan Qawafi): Aesthetics of Rhythm and Ethics in Syi'ir Ber-Qafiyah Lam by Harits Al-Makhzumi (Arudh and Qawafi Analysis) - Syifa Nurhaliza Rahman; Rohanda Rohanda; Irfan Addriadi (JBSI: Jurnal Bahasa dan Sastra Indonesia, 2026)
This study aims to reveal the aesthetic elements of rhythm and ethics contained in Harits Al-Makhzumi's qafiyah lam poetry through the approach of arudh and qawafi science. The focus of this study includes the identification of arudh and qawafi patterns used by the poet, as well as the moral values contained therein. This study departs from the view that poetry not only contains the beauty of sound structure, but also contains ethics that reflect moral values. This study uses a qualitative approach with a descriptive analytical research method, by combining the arudh (rhythm) and qawafi (rhyme) science approaches in analyzing poetry patterns, as well as the ethical approach according to Ibn Miskawaih to reveal moral values in literary works. This approach was chosen because the study aims to describe in depth the aesthetics of rhythm (arudh and qafiyah forms) and ethics contained in Harits Al-Makhzumi's qafiyah lam poetry. The data of this research were obtained from the text of Harits Al-Makhzumi's diwan through the technique of listening and noting, then analyzed using the theory of arudh and qawafi, as well as ethics according to Ibn Miskawaih, to interpret the moral values contained therein. The results of the study show that the syi'ir ber-qafiyah lam by Harits Al-Makhzumi uses 5 types of bahar, namely: towil, basith, romal, kamil tam, and khofif with different variations of zihaf and illat, as well as the form of qafiyah found at the end of the verse of the syi'ir. From the ethical aspect, 4 moral values were found according to Ibn Miskawaih, namely hikmah (wisdom), syaja'ah (courage), 'ifah (self-restraint), and 'adalah (just). This research is expected to contribute to the development of Arabic literary studies. Especially combining the aesthetics of rhythm and ethics in syi'ir.